PROPOLIS AND BEE VENOM IN DIABETIC WOUNDS; A POTENTIAL APPROACH THAT WARRANTS CLINICAL INVESTIGATION - Al-waili, Noori; Hozzein, Wael N.; Badr, Gamal; Al-Ghamdi, Ahmed; Al-Waili, Hamza; Salom, Khelod; Al-Waili, Thia (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Wound healing in diabetes mellitus is a complex multi-stage process that requires the proper function of multiple systems. Themechanisms of impaired wound healing of diabetic wounds are still poorly understood. Therefore, various interventions are being used for woundmanagement without great success. Bee products have various properties that make them an important addition to the diabetic wound management.Methods: This review summarized previous and recently published papers of the effects of two bee products, propolis and bee venom, on the woundhealing. The main results were obtained from preclinical experimentation.Results: Diabetes mellitus compromises immune system, increases infections, impairs wound healing, and affects cells and factors involved in thewound healing. There is an increasing interest in natural products in modern medicine as part of disease management. Bee products are naturalsubstances that others and we have explored some of their biological activities and applications in the treatment of various diseases. Some of theseproducts are bee venom and propolis. These products have analgesic, antioxidant, antimicrobial, and anti-inflammatory properties. In addition, bothpropolis and bee venom contain considerable amounts of antioxidants that have a great role in accelerating wound healing.Conclusion: There is sound rationality and scientific data for using propolis and bee venom in diabetic wound healing. We believe that topicalapplication of propolis in addition to bee venom might have a place in repairing damaged tissues and accelerating the healing of diabetic wounds.